Microsoft windows security resource kit - Smith, Ben 1975- (Microsoft Press, 2005)
Fully updated and revised, this official MICROSOFT RESOURCE KIT delivers the in-depth information and tools you need to plan and implement a comprehensive security-management strategy for Windows-based clients, servers, and networks.
Includes bibliographical references and index. - Print version record
Keywords: Microsoft Windows (Computer file); Computer security; Computer networks -- Security measures; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Computer networks; Security measures; Engineering & Applied Sciences; Computer Science; Microsoft